Comparison Of Road Traffic Noise At Residential Areas In Nibong Tebal, Penang And Klang Valley - Mohamad Nor, Nur Atiqah (Universiti Sains Malaysia, 2018)
This study focuses on the monitoring of road traffic noise between Nibong Tebal, Penang (Medium density) and Klang Valley (High density) study areas. The objectives of this study were to investigate the level of traffic noise at medium and high density studied site and to characterize the traffic composition on the road nearby study areas. A precision Sound Level Meter (SLM) Class One used in the measurements. The measurements were taken for 15 minutes (the sound level meter recorded every oneminute noise level) in the residential area and from 0800 – 0900 (morning), 1400-1500 (evening) and 2200 – 2300 (night). Equivalent Continuous Sound Level (Leq ), Sound Level exceeded 10% of the measurement period (L10), Sound level exceeded 90% of the measurement (L90) and maximum noise level (Lmax) were measured to assist in assessing the existing noise level at the selected sites. Manual Traffic Count was measured simultaneously with noise level and speed of vehicle. Traffic composition data in this study is categorized into four types, which Car and Van, Motorcycle, Medium Lorries and Heavy Vehicles according to the Arahan Teknik Jalan (8/86), A Guide on Geometric Design of Roads. Heavy Lorries involves a vehicle with more than 2 axles such as Lorry and Buses. Result showed that the monitored noise levels in term of LAeq in residential area ranged between 62 dB(A) to 74.25 dB(A) for weekday and 61.2 dB(A) to 75.59dB(A) for weekend for both study sites. These levels highly exceeded the Maximum Permissible Sound Level by Receiving Land Use for Planning and New Development.